Study of Effectiveness of Cooperative Learning on Academic Achievement of Mathematics of Class x Students - Rakesh Kumar,; Moushmi Kumari, (JOURNAL OF INDIAN EDUCATION, 2021)
Teamwork is a hallmark of the digital era, and cooperative learning provides a sustainable platform where all students develop beneficial lifelong learning skills. Mathematics makes our lives systematic and prevents chaos and students require both cognitive and practical experience throughout their mathematics education. The academic achievement in mathematics of students taught through different activities of the cooperative learning method is better than the traditional method. Students develop their logical thinking, the problem solving and decision making skills through the applicability of concepts with the learners, resulting in social, communication, teamwork, conflict management and leadership abilities. They are motivated to work with cooperation and respect everyone’s presence. Students receive feedback, challenge one another, and teach, encourage and motivate their teammates. It gives them an opportunity to learn from each other in a healthy, friendly and welcoming environment. Thus, cooperative learning is an effective method which helps students attain their life goals and enhance their understanding of the world around them. It also provides them with better opportunities and improves their quality of life.